Imbalance and drivers of carbon emissions embodied in trade along the Belt and Road Initiative. (15th December 2020) - Lu, Qinli; Fang, Kai; Heijungs, Reinout; Feng, Kuishuang; Li, Jiashuo; Wen, Qi; Li, Yanmei; Huang, Xianjin
Highlights: Region contributed to 50% of global CO2 emissions and 92% of increase in 1995–2015. Region was a net exporter of trade-embodied emissions despite high carbon intensity. Carbon leakage has gradually moved from China and India to other developing nations. The nations had diverse trends of carbon footprint due to technological differences. The drivers of changes in regional CO2 emissions varied across nations and over time. Abstract: A continuous growth of international trade, especially between developing countries, has greatly increased carbon dioxide (CO2 ) emissions associated with energy consumption over the past two decades. Given the more intensified intraregional cooperation and trade within the Belt and Road Initiative (BRI), this study aims to trace the imbalance of CO2 embodied in trade between nations in BRI and the rest of the world, providing new insights into the drivers of emissions growth by contrasting consumption, production and technological differences-based perspectives. Results indicate that the BRI contributed to over 50% of global carbon footprint and 92% of its increase in 1995–2015. The BRI was a net exporter of trade-embodied emissions, whose technological-adjusted carbon footprint remained remarkably large due to comparatively high carbon intensity. Geographically, carbon leakage has gradually moved from China and India to other BRI countries, especially to Southeast Asia, West Asia and Africa. Technological change was the key driver of emissions reduction, followed by the change in industrial structure. The growth in final demand per capita was the most important driver for the growth of CO2 emissions in BRI. Improving carbon efficiency remains a critical step for BRI nations to slow down not only emissions growth but also carbon leakage. The paper managed to provide novel insights into the carbon leakage in BRI by contrasting the consumption, production and technological differences-based perspectives, thus being able to better inform policymakers on region-specific low-carbon transition and global climate governance.